PENGARUH KOMPETENSI KERJA DAN STRES KERJA TERHADAP KINERJA (STUDI KASUS PADA KARYAWAN PT. ARA SHOES INDONESIA SEMARANG) - Saragih, Theresia Dwi Putri; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2018)
In an effort to improve employee performance, work stress and job competence is very important to be considered by every company. The problem of this research is low employee performance at PT. Ara Shoes Indonesia Semarang. The factors that affect the labour performance are work competence and job stress. This study uses quantitative data derived from primary sources that have been collected through questionnaires. The population of this study is 1800 employees working in PT. Ara Shoes Indonesia Semarang, with a sample of 100 respondents. The sampling technique used is simple random sampling. While the data analysis technique used is the method of validity test, reliability test, correlation coefficient, coefficient of determination, multiple linear analysis, and hypothesis testers (t test and F test). The results of this study indicate a positive influence of work competence tarhadap labor performance seen from the coefficient of regression X1 is worth 0.980. Work stress negative effect on labor performance, seen from value of regression coefficient X2 is -0,626. There is a simultaneous influence of work competence and job stress on performance.Suggestion given by researcher for PT. Ara Indonesia Semarang follows. At is regured pay attention to education, work rules, work experience and understanding of work to improve work competence. In addition, the company should also pay attention to employee's mistakes in work, difficulty in communicating the partners, the heavy given to the employee, and pay attention to the work so as not to physically harm so as to reduce job stress on the employees.